1992
DOI: 10.1002/jcp.1041530305
|View full text |Cite
|
Sign up to set email alerts
|

Localization of p35 (annexin I, lipocortin I) in normal adult rat kidney and during recovery from ischemia

Abstract: The 35-kDa protein (p35, lipocortin I, annexin I), originally discovered as a Ca(++)-dependent substrate for the EGF receptor tyrosine kinase, binds Ca++ and phospholipids, is developmentally regulated in embryos and has restricted expression in adults. Immunohistochemistry of normal rat kidney shows that p35 is enriched in epithelia of Bowman's capsule, the macula densa, and medullary/papillary collecting ducts, suggesting that p35 is related to specialized renal functions. Light staining is observed in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
28
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 32 publications
9
28
0
Order By: Relevance
“…In a normal kidney ANXA1 is mainly found in Bowman's capsule epithelium, macula densa and medullary and papillary collecting ducts, with light staining at the thick ascending limb. After ischemia/reperfusion, ANXA1 renal tissue expression increases significantly [42], as observed in the present study. These data suggest that endogenous ANXA1 increase might be an attempt to protect cell function and structure against ischemia reperfusion injury [43].…”
Section: Discussionsupporting
confidence: 90%
“…In a normal kidney ANXA1 is mainly found in Bowman's capsule epithelium, macula densa and medullary and papillary collecting ducts, with light staining at the thick ascending limb. After ischemia/reperfusion, ANXA1 renal tissue expression increases significantly [42], as observed in the present study. These data suggest that endogenous ANXA1 increase might be an attempt to protect cell function and structure against ischemia reperfusion injury [43].…”
Section: Discussionsupporting
confidence: 90%
“…These polyclonal antisera are effective at 1:8000 dilution, they identify LC1-ir in identical cell types in both frozen and paraffin sections, and the staining is completely abolished by pre-incubation with purified LC1. Studies in kidney have shown that pathophysiological changes in levels of LC1-ir quantified in tissue sections corresponded precisely with levels measured from immunoblot (Western) analysis (McKanna et al 1992).…”
Section: Immunochemistry Of Lipocortinmentioning
confidence: 60%
“…Mean density on a scale of 0-255 was determined for Ͼ 50 cells per specimen and was standardized as a percentage of the density range defined by the kidney specimen on the same slide. Because previous studies (McKanna et al 1992) have demonstrated consistently strong LC1-ir in the medullary collecting ducts of normal rat kidney, the density of this staining was taken as 100% and assigned a rank of 4 ϩ ; unstained regions of the kidney cortex defined the density of background (0% ϭ Ϫ ). Other ranks were assigned from intervals on a linear scale from these endpoints: Ͻ 10%, Ϫ ; 10-20%, ϩ / Ϫ ; 21-40%, ϩ ; 41-60%, 2 ϩ ; 61-80%, 3 ϩ ; and 81-100%, 4 ϩ .…”
Section: Quantitative Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Ischemic renal injury was produced in male Sprague-Dawley rats weighing 150-200 g. Unilateral renal ischemia was induced by surgical clamping of the left renal artery for 50 min as previously described (35). After removal of the clamp to allow reperfusion for the indicated periods, rats were killed and kidneys were removed for analysis.…”
Section: Methodsmentioning
confidence: 99%